Retention of Mother Tongue as Instructional Language at the Junior High School Level in Ghana: Teachers' and Students' Perspectives - Nyamekye, Ernest (Social Education Research, 2022)
The early-exit transitional education policy in Ghana demands that teachers at the junior high school level exclusively use English as the language of instruction. However, there are numerous reports that some teachers constantly violate the implementation of this policy by retaining the mother tongue (L1) of students as the instructional language. The present explanatory case study, therefore, aimed to investigate the rationale behind the retention of students' L1 (Twi) as the language of instruction, as well as how such practice affects students' academic progress. The study included five public schools in the Sunyani-West District of the Bono Region, Ghana. Data from 100 participants (including 25 teachers and 75 students) were gathered through classroom observations, focus group discussions, and interviews. It was found that teachers retain students' L1 at the junior high school level because they believe it is the most effective means of ensuring a better understanding of lessons, which would otherwise be difficult given the low English proficiency of the students as well as some teachers. The findings of the study also indicated that students had greater interest in L1-based instruction because they believed that the use of their L1 created an enabling environment that promoted active participation and learner-centred pedagogy. In this regard, it was recommended that, given the difficulties teachers and students encounter in implementing the early-exit policy, the late-exit transitional education policy should be adopted by the Ghana Education Service.